1976
DOI: 10.1029/jc081i012p01971
|View full text |Cite
|
Sign up to set email alerts
|

Variations in coastal temperatures on the southern and central California coast

Abstract: Th.e resu.its of a time series analysis of several years of coastal ocean temperature records are presented for d1scuss1on. The records have been analyzed by using digital filtering, covariance and spectral analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Hueneme-nearly 200 km apart) and suggested that coherence is also found in the near-coastal region. List and Koh (1976) described the low frequency (period >4 months) components of nearshore surface temperatures as highly correlated throughout the entire Southern California coast. This bightwide coherence, at least at annual to interannual frequencies, can bc considered as caused by large-scale natural phcnomcna, such as seasonal change, El Niiio events, or other changes in the bight circulation pattern.…”
Section: Physical Oceanography Of the Bightmentioning
confidence: 99%
“…Hueneme-nearly 200 km apart) and suggested that coherence is also found in the near-coastal region. List and Koh (1976) described the low frequency (period >4 months) components of nearshore surface temperatures as highly correlated throughout the entire Southern California coast. This bightwide coherence, at least at annual to interannual frequencies, can bc considered as caused by large-scale natural phcnomcna, such as seasonal change, El Niiio events, or other changes in the bight circulation pattern.…”
Section: Physical Oceanography Of the Bightmentioning
confidence: 99%
“…On the other hand, wind forcing explains diurnal and lower frequency temperature variability (Cairns and LaFond, 1966;List and Koh, 1976;Dorman and Palmer, 1981). Ekman upwelling is weak in the Bight nearshore (Winant and Bratkovich, 1981;Jackson, 1986), but energetic in northern Baja California (Barton and Argote, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…SST spectra along the California coast over several years exhibited strong peaks at 14.7 days; these peaks were probably the result of tidal aliasing and/or the spring and neap tides (List and Koh, 1976 (Skogsberg, 1936 (Huyer et al 1979).…”
mentioning
confidence: 99%
“…138) surface temperature fields (Barnett and Patzert, 1980; Halliwell Reid et al (1958) and List and Koh (1976 1972-73, 1976-77, 1979-80, and 1982-83 (1) core varied between 25 and 50km offshore, (2) vertical extent varied between about 50 and 125m, and (3) width was of the order of 20km. (Breaker, 1982 …”
mentioning
confidence: 99%